Humans and Mice Display Opposing Patterns of “Browning” Gene Expression in Visceral and Subcutaneous White Adipose Tissue Depots - Zuriaga, Maria A.; Fuster, Jose J.; Gokce, Noyan; Walsh, Kenneth (Frontiers in Cardiovascular Medicine, 2017)
Visceral adiposity is much more strongly associated with cardio-metabolic disease in humans than subcutaneous adiposity. Browning, the appearance of brown-like adipocytes in the of white adipose tissue (WAT), has been shown to protect mice against metabolic dysfunction, suggesting the possibility of new therapeutic approaches to treat obesity and type 2 diabetes. In mice, subcutaneous WAT depots express higher levels of browning genes when compared with visceral WAT, further suggesting that differences in WAT browning could contribute to the differences in the pathogenicity of the two depots. However, the expression of browning genes in different WAT depots of human has not been characterized. Here, it is shown that the expression of browning genes is higher in visceral than in subcutaneous WAT in humans, a pattern that is opposite to what is observed in mice. These results suggest that caution should be applied in extrapolating the results of murine browning gene expression studies to human pathophysiology.